Akhenaten as the Early Morning Light: Revisiting the “Consecration” Ritual in Amarna - David, Arlette.
One of the typical images of Atenist iconography involves Amenhotep IV/Akhenaten extending the ‘b3/s?m/?rp/?w-‘ scepter in the light of Aten, near offerings; known from various contexts in Karnak and Amarna, it flourishes in all phases of his reign. The ritual scene is traditionally characterized as a “consecration of offerings” modeled on similar scenes belonging to the royal iconographic repertoire since the Middle Kingdom. A new approach and understanding of the ritual gesture is proposed, according to the iconography and texts of the Amarna tombs: this context offers an insight into the time and loci of this performance and hints at a possible explanation of the Atenist cultic motif. A reappraisal of the famous double scene in room alpha of the royal tomb according to the funerary iconographic program adopted in Amarna is proposed, as well as general conclusions on the staging of the morning ritual in Amarna.